Evaluation of a Virtual Reality Percutaneous Nephrolithotomy (PCNL) Surgical Simulator - Sainsbury, Ben; Łącki, Maciej; Shahait, Mohammed; Goldenberg, Mitchell; Baghdadi, Amir; Cavuoto, Lora; Ren, Jing; Green, Mark; Lee, Jason; Averch, Timothy D.; Rossa, Carlos (Frontiers in Robotics and AI, 2020)
Percutaneous Nephrolithotomy is the standard surgical procedure used to remove large kidney stones. PCNL procedures have a steep learning curve; a physician needs to complete between 36-60 procedures, to achieve clinical proﬁciency. Marion Surgical K181 is a virtual reality surgical simulator, which emulates the PCNL procedures without compromising the well-being of patients. The simulator uses a VR headset to place a user in a realistic and immersive operating theatre, and haptic force-feedback robots to render physical interactions between surgical tools and the virtual patient. The simulator has two modules for two different aspects of PCNL kidney stone removal procedure: kidney access module where the user must insert a needle into the kidney of the patient, and a kidney stone removal module where the user removes the individual stones from the organ. In this paper, we present user trials to validate the face and construct validity of the simulator. The results, based on the data gathered from 4 groups of users independently, indicate that Marion’s surgical simulator is a useful tool for teaching and practicing PCNL procedures. The kidney stone removal module of the simulator has proven construct validity by identifying the skill level of different users based on their tool path. We plan to continue evaluating the simulator with a larger sample of users to reinforce our ﬁndings.